Associations of 4AT with mobility, length of stay and mortality in hospital and discharge destination among patients admitted with hip fractures. (8th December 2019) - Lisk, Radcliffe; Yeong, Keefai; Enwere, Peter; Jenkinson, Josie; Robin, Jonathan; Irvin-Sellers, Melanie; Fluck, David; Osmani, Ahmad; Sharmin, Rifat; Sharma, Pankaj; Fry, Christopher H; Han, Thang S
Abstract: Background: the 4AT (Alertness, Abbreviated Mental Test-4, Attention and Acute change or fluctuating course), a tool to screen cognitive impairment and delirium, has recently been recommended by the Scottish Intercollegiate Guidelines Network. We examined its ability to predict health outcomes among patients admitted with hip fractures to a single hospital between January 2018 and June 2019. Methods: the 4AT was performed within 1 day after hip surgery. A 4AT score of 0 means unlikely delirium or severe cognitive impairment (reference group); a score of 1–3 suggests possible chronic cognitive impairment, without excluding possibility of delirium; a score ≥ 4 suggests delirium with or without chronic cognitive impairment. Logistic regression, adjusted for: age; sex; nutritional status; co-morbidities; polypharmacy; and anticholinergic burden, used the 4AT to predict mobility, length of stay (LOS), mortality and discharge destination, compared with the reference group. Results: from 537 (392 women, 145 men: mean = 83.7 ± standard deviation [SD] = 8.8 years) consecutive patients, 522 completed the 4AT; 132 (25%) had prolonged LOS (>2 weeks) and 36 (6.8%) died in hospital. Risk of failure to mobilise within 1 day of surgery was increased with a 4AT score ≥ 4 (OR = 2.4, 95% confidence interval [CI] = 1.3–4.3). Prolonged LOS was increased with 4AT scores of 1–3 (OR = 2.4, 95%CI = 1.4–4.1) or ≥4 (OR = 3.1, 95%CI = 1.9–6.7). In-patient mortality was increased with a 4AT score ≥ 4 (OR = 3.1, 95%CI = 1.2–8.2) but not with a 4AT score of 1–3. Change of residence on discharge was increased with a 4AT score ≥ 4 (OR = 3.1, 95%CI = 1.4–6.8). These associations persisted after excluding patients with dementia. 4AT score = 1–3 and ≥ 4 associated with increased LOS by 3 and 6 days, respectively. Conclusions: for older adults with hip fracture, the 4AT independently predicts immobility, prolonged LOS, death in hospital and change in residence on discharge.